PENGARUH INTERNAL SERVICE QUALITY TERHADAP KEPUASAN KARYAWAN PADA PT. BANK RIAU KEPRI - Bakri, Syamsul; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2014)
This study aims to analyze and examine the influence of internal service quality to satisfaction of employees at PT. Bank Riau Kepri The study was a descriptive design as a form of conclusive research . This design is chosen because the study was designed to describe the characteristics or functions of objects and phenomena observed or surveyed, so it can be concluded through a series of statistical tests , including hypothesis testing. The population in this study were all employees of the PTBank Riau Kepri, amounting to 1,751 people. Sampling was done by using porportionally, so that the number of samples in this study were 317 men. To determine the influence of an independent variable on the dependent variable used multiple linear regression analysis model. As for testing the hypothesis using statistical tests . The results showed that (1) the availability of equipment has negative influence but not significant on employee satisfaction, (2) policies and procedures has positive influence but not significant on employee satisfaction, (3) team work has positive influence but not significant on employee satisfaction, (4) management support has positive influence but not significant on employee satisfaction, (5) the alignment of the target significantly has positive influence on employee satisfaction, (6) training has positive influence but not significant on employee satisfaction, (7) communication significantly has positive influence on employee satisfaction, and (8) rewards and recognition significantly has positive influence on employee satisfactionKeywords : Internal Service Quality and Employee Satisfaction